Diversidad genética de dos poblaciones del caracol Strombus gigas (Gastropoda: Strombidae) en Yucatán, México, con microsatélite - Zamora-Bustillos, Roberto (Universidad de Costa Rica, 2011)
The pink conch Strombus gigas is an important fisheries resource in the Caribbean region, including the Yucatán Peninsula. We analyzed the genetic diversity and genetic structure of two populations (Alacranes Reef and Chinchorro Bank) with the use of five microsatellite molecular markers. The results indicate that the two populations are in the same rank of genetic diversity (He), from 0.613 to 0.692. Significant deviation from H-WE was observed in the both populations due to deficit to heterozygotes, this was attributed to inbreeding as a consequence of over-fishing; nevertheless, other possible causes considered are mixing of individuals from two or more populations, and the existence of null alleles. Levels of genetic differentiation indicated the existence of a single homogenous population in the Yucatan Peninsula (FST de 0.003, p=0.49), which fits with highest levels of gene flow is significant (2.3 individuals) between both populations. Results from this study support the hypothesis that S. gigas is part of a single panmictic population in the Yucatan Peninsula; therefore, this fishery resource should be regulated the same way for both areas.